2018
DOI: 10.1002/14651858.cd010649.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Pro-coagulant haemostatic factors for the prevention and treatment of bleeding in people without haemophilia

Abstract: Pro-coagulant haemostatic factors for the prevention and treatment of bleeding in people without haemophilia (Review)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
29
0
3

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 86 publications
0
29
0
3
Order By: Relevance
“…57 Randomized trials are increasingly informing optimal practice (eg, tranexamic acid, plasma), but the size and methodological quality of all the studies varies very considerably. 58 Exposure to extracorporeal circulation circuits and consequent blood-circuit surface interaction triggers a cascade of events that promote both bleeding and thrombosis. Platelet activation is a central event that contributes to both.…”
Section: Fviii-parg612mentioning
confidence: 99%
“…57 Randomized trials are increasingly informing optimal practice (eg, tranexamic acid, plasma), but the size and methodological quality of all the studies varies very considerably. 58 Exposure to extracorporeal circulation circuits and consequent blood-circuit surface interaction triggers a cascade of events that promote both bleeding and thrombosis. Platelet activation is a central event that contributes to both.…”
Section: Fviii-parg612mentioning
confidence: 99%
“…However, to date there have been no randomised controlled trials (RCT) that have compared the clinical efficacy and safety of PCC versus FFP in bleeding cardiac surgery patients who are not taking vitamin K antagonists (e.g., warfarin), and this was highlighted in a recent systematic review [4]. Several observational studies have demonstrated that PCC is safe in this setting and that its administration is associated with reduced blood transfusion requirements, albeit with no difference in other outcomes [5, 6].…”
Section: Introductionmentioning
confidence: 99%
“…However, to date there have been no randomized controlled trials (RCT) that have compared the clinical efficacy and safety of PCC versus FFP in bleeding cardiac surgery patients, who are not taking vitamin K antagonists (like warfarin), and this was highlighted in a recent systematic review [4].…”
Section: Introductionmentioning
confidence: 99%